Analisis Bibliometrik: Interlibrary Loan pada Perpustakaan Berdasarkan Web of Science - Handari Niken Anggraini; Imam Yuadi (Perpustakaan Nasional, 2024)
The massive use of the Internet has a pretty significant impact on information-seeking behavior. That's why the public's need for information is increasing. It has an impact on information providers, especially libraries. A library must be able to adapt to the needs of users, especially in services and collections. In order to meet the needs of librarians, libraries use the interlibrary loan method, in which libraries cooperate with other libraries. The library can not only receive material but also supply the library's collection material. The aim of this research is to learn about the development of publications on interlibrary loans in libraries over the last 10 years (2013-2023) which includes key information, annual productions, core sources by Bradford’s Law, quotations, affiliations, trend topics, and authors. Using the